2015
DOI: 10.1016/j.socscimed.2014.10.032
|View full text |Cite
|
Sign up to set email alerts
|

A scalable climate health justice assessment model

Abstract: This paper introduces a scalable “climate health justice” model for assessing and projecting incidence, treatment costs, and sociospatial disparities for diseases with well-documented climate change linkages. The model is designed to employ low-cost secondary data, and it is rooted in a perspective that merges normative environmental justice concerns with theoretical grounding in health inequalities. Since the model employs International Classification of Diseases, Ninth Revision Clinical Modification (ICD-9-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
0
9
0
2
Order By: Relevance
“…49 Another study projected that the cost of asthma could increase by more than 5% due to climate change. 50 A study based in Nepal estimated that the asthma treatment cost per case is US $73.78 without including the costs of lost productivity. 51 The per case cost of asthma is quite high in developed countries, estimated to be US $420 in 2006 in the US.…”
Section: -Probit Regressionmentioning
confidence: 99%
“…49 Another study projected that the cost of asthma could increase by more than 5% due to climate change. 50 A study based in Nepal estimated that the asthma treatment cost per case is US $73.78 without including the costs of lost productivity. 51 The per case cost of asthma is quite high in developed countries, estimated to be US $420 in 2006 in the US.…”
Section: -Probit Regressionmentioning
confidence: 99%
“…The underlying principle of the proposed framework is an adaptation strategy’s potential for climate justice that serves as proxy indicator for effectiveness in adaptation evaluation. Our definition of climate justice refers to distributional justice [ 27 ] of the burden of adverse health effects, closely linked to the concept of environmental justice in the Public Health context. Environmental justice is based on the notion that environmental hazards and exposures disproportionately affect people with lower socio-economic capital, people of color, people in lower income regions or city districts, children, and people with less political power [ 22 ].…”
Section: Results: a Theoretical Framework For Adaptation Evaluatiomentioning
confidence: 99%
“…Considering the above mentioned unequally distributed vulnerabilities to adverse effects, evaluation approaches that specifically incorporate or address these aspects might be useful [ 27 , 28 ].…”
Section: Introduction: Climate Change Affects Human Healthmentioning
confidence: 99%
“…Health and social inequities among low socioeconomic and minority populations can be attributed to a number of factors related to increased hospitalizations costs including, environmental justice issues, healthcare access and utilization, and lack of education [ 30 ]. A number of studies have also suggested that these marginalized groups face unequal exposures to climate hazards, referred to as the “climate gap” [ 40 , 41 ]. Our data lack the ability to answer these specific questions, though we have identified significant differences in HRI hospitalization costs among these marginalized populations, further research is needed to explore how issues of environmental justice, healthcare access, and health behaviors relate to HRI hospitalizations and increased hospital costs.…”
Section: Discussionmentioning
confidence: 99%